Great essays an introduction to writing essays - Folse, Keith S. (Houghton Mifflin Company, 2004)
Great Essays shows students how to write effective essays and provides practice in a variety of rhetorical patterns. Students will learn to concentrate on grammar while practicing the cohesive elements of writing.